Inflammatory markers are associated with ventilatory limitation and muscle dysfunction in obstructive lung disease in well functioning elderly subjects. Issue 1 (11th November 2005) - Yende, S; Waterer, G W; Tolley, E A; Newman, A B; Bauer, D C; Taaffe, D R; Jensen, R; Crapo, R; Rubin, S; Nevitt, M; Simonsick, E M; Satterfield, S; et al.
Abstract : Background: Inflammatory markers are increased in chronic obstructive pulmonary disease (COPD) and are hypothesised to play an important part in muscle dysfunction and exercise intolerance. Methods: The Health Aging and Body Composition (Health ABC) study is a prospective observational cohort of well functioning individuals aged 70–79 years. A cross sectional analysis of the baseline data was conducted to examine the association between inflammatory markers and ventilatory limitation, muscle strength, and exercise capacity. These associations were compared in participants with and without obstructive lung disease (OLD). Results: Of the 3075 participants enrolled in the Health ABC cohort, OLD was identified by spirometric testing in 268 participants and 2005 participants had normal spirometric results. Of the participants with OLD, 35%, 38%, and 27% participants had mild, moderate, and severe OLD, respectively. Participants with OLD had lower quadriceps strength (102.5 Nm v 108.9 Nm, p = 0.02), lower maximum inspiratory pressure (64.7 cm H2 O v 74.2 cm H2 O, p<0.0001), higher systemic interleukin (IL)-6 levels (2.6 pg/ml v 2.2 pg/ml, p<0.0001), and higher C-reactive protein (CRP) levels (3.5 mg/l v 2.5 mg/l, p<0.0001) than those with normal spirometry. In participants with OLD and those with normal spirometry, forced expiratory volume in 1 second (FEV1 ) was associated with IL-6 (adjusted regression coefficients (β) = −5.3 (95% CI −9.1 to−1.5) and −3.1 (95% CI −4.3 to −1.9), respectively). IL-6 and TNF were also associated with quadriceps strength among participants with OLD and those with normal spirometry (β = −6.4 (95% CI −12.8 to −0.03) and −3.4 (95% CI −5.4 to −1.3), respectively, for IL-6 and β = −10.1 (95% CI −18.7 to −1.5) and −3.8 (95% CI −7 to −0.6), respectively, for TNF). IL-6, quadriceps strength, and maximum inspiratory pressures were independent predictors of reduced exercise capacity in both groups. Conclusions: In well functioning elderly subjects with or without OLD, IL-6 is associated with reduced FEV1, quadriceps strength, and exercise capacity.